Prognostic models for depression and post-traumatic stress disorder symptoms following traumatic brain injury: a CENTER-TBI study - Kelly Jones; Antonio Belli; Suzanne Polinder; Emmanuel Stamatakis; Hester F Lingsma; Dick Tibboel; Ronny Beer; Raimund Helbok; Horia Ples; Ari Ercole; Peter Cameron; Marek Czosnyka; et al. (BMJ Mental Health)
Background Traumatic brain injury (TBI) is associated with an increased risk of major depressive disorder (MDD) and post-traumatic stress disorder (PTSD). We aimed to identify predictors and develop models for the prediction of depression and PTSD symptoms at 6 months post-TBI.Methods We analysed data from the Collaborative European NeuroTrauma Effectiveness Research in Traumatic Brain Injury study. We used linear regression to model the relationship between predictors and depression (Patient Health Questionnaire-9) and PTSD symptoms (PTSD Checklist for Diagnostic and Statistical Manual for Mental Health Disorders Fifth Edition). Predictors were selected based on Akaike’s Information Criterion. Additionally, we fitted logistic models for the endpoints ‘probable MDD’ and ‘probable PTSD’. We also examined the incremental prognostic value of 2–3 weeks of symptoms.Results We included 2163 adults (76% Glasgow Coma Scale=13–15). Depending on the scoring criteria, 7–18% screened positive for probable MDD and about 10% for probable PTSD. For both outcomes, the selected models included psychiatric history, employment status, sex, injury cause, alcohol intoxication and total injury severity; and for depression symptoms also preinjury health and education. The performance of the models was modest (proportion of explained variance=R2 8% and 7% for depression and PTSD, respectively). Symptoms assessed at 2–3 weeks had a large incremental prognostic value (delta R2=0.25, 95% CI 0.24 to 0.26 for depression symptoms; delta R2=0.30, 95% CI 0.29 to 0.31 for PTSD).Conclusion Preinjury characteristics, such as psychiatric history and unemployment, and injury characteristics, such as violent injury cause, can increase the risk of mental health problems after TBI. The identification of patients at risk should be guided by early screening of mental health.